Regional Model Bit’s : A New Down For the Developing Countries - Abdallah Mohamed Othman El Nofely; Rehna Gul (Fakultas Hukum, Universitas Warmadewa, 2021)
Foreign direct investment (FDI) plays a crucial role in the economic sector, particularly in developing countries. BIT lays down instrumental principles which help to protect investors’ establishments in host states, by inter alia encouraging prompt compensation in case of expropriation. Governments need FDIs to gear up their economic growth, advance technology, and scale down unemployment. Most scholarly writings are in favor that BIT is a necessary tool for promoting FDIs, however this study takes a different approach and categorically unveils the draw backs of BIT in developing countries by highlighting some of the contentious provisions that have sparked unprecedented legal, economic, sociopolitical and diplomatic strife between the host countries, investors and investors’ home countries. Therefore, the author proposes development for regional Model BITs that would go in line with national laws to curtail the persisting sovereignty and socio-economic challenges.